The Effectiveness Of Lesson Study On Differentiated Instruction Among Mathematics Head Panels In District Of Port Dickson - Lau Sai Ping; Ilda Salwani binti Ameer Hamza; Ruzihan binti Abdullah; Murni binti Mohamad Yasin; Suzalin binti Zaini Sooria; Lee Bee Bee (Universitas Muhammadiyah Gresik, 2020)
This study is to examine the effectiveness of lesson study on differentiated instruction among Mathematics headpanels in district of Port Dickson, Malaysia. Teachers who received substantial professional development canboost their students’ achievement. The effectiveness of professional development practice is being measuredby the heads of panel understanding about differentiated instruction and the application of differentiatedinstruction in the classroom. Teachers often struggle to deliver mathematics lesson effectively in classroom dueto different learning styles and students’ mixed abilities in the classroom. Some students learn at a slower paceand some in advance stage. The activities provided by teachers may work best for some students but will notwork for others. During lesson, teachers often assign tasks, which many students end up with disappointmentand confusion. Students become passive learners and teacher felt frustrated. Therefore, differentiatedinstructions make sense because it offers different paths to understand content, process and product. The aimof the present study was to obtain information from the school teachers in the implementation and planning ofdifferentiated instruction in teaching and learning. Moreover, the research team were interested in knowing thestrategy of differentiated instruction used in teaching and learning that support quality teaching. This studyinvolved 33 mathematics head panels from national primary schools in district of Port Dickson who volunteeredto participate in this study. In this programme, heads of panel will be able to share their experiences inconducting and implementing differentiated instructions in classroom among peers in the district. Structuredquestionnaires and interviews were used in this qualitative study to collect data. Results indicated that thelesson study carried out by the Port Dickson District Education Office is effective. Furthermore, the lessonstudy that were carried out by heads of panel in theirs school managed to boost self confidence among theseheads of panel. In fact, they showed willingness to share best practices to all mathematics teachers in the district205